Coronavirus–associated enteritis in a quail farm - Antonio Camarda; Antonio Lavazza; Eleonora Lorusso; Giordano Bruni; Vito Martella; Elena Circella (Italian Journal of Animal Science, 2010)
An enteric syndrome observed in semi-intensively reared quails is described. The affected birds showed depression, severe diarrhoea and dehydration. The mortality occurred particularly in young birds. At necropsy, the prominent lesion was catarrhal enteritis. Laboratory investigations demonstrated the presence of coronavirus in the gut of dead animals. No additional pathogens were detected. To our knowledge, this is the first evidence for the presence of CoVs in quail with enteritis.